Heidegger's way of being - Capobianco, Richard, 1957- (New studies in phenomenology and hermeneutics (Toronto, Ont.), 2014)
Richard Capobianco makes the case that the core matter of Heidegger's lifetime of thought was Being as the temporal emergence of all beings and things.